Ensino Comercial na I República à luz dos debates parlamentares - Magalhães, Marcelo (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The purpose of the present work is to deepen the knowledge about Portuguese business education during the Portuguese First Republic, through the interest expressed by the government elites (deputies, senators and ministers) in parliamentary interventions, and in the proposals and law projects presented in the Chamber of Deputies and in the Senate between 1911 and 1926.